Algorithm of Dynamic Model Structural Identification of the Multivariable Plant - Васюхіна, І.М.; Кузнєцова, К.С. (Proceedings of National Aviation University (archive), 2005)
The approach which tended in this article is based on the theorem of hypotheses (Bayes' formula), which one is intended for definition of the verity of alerts for the automated systems of guards relevant and apart of relevant objects. This method allows to execute synthesizing a system from rather accident-sensitive, but not of expensive subsystems – components.